Mortality in children under 5: prevalence of congenital malformations and its associated demographic variables - Rozita Zakaria,; Lim, Ming Tsuey; Norsiah Ali,; Nurainul Hana Shamsuddin,; Norseha Isnin,; Siti Hafsah Abdul Halim,; Aminah Bee Mohd Kasim,; Rozita Abd Rahman,; Fauzia Abd Majid,; Kok, Sim Hui; Norizzati Ismail Bukhary,; Rawa Bau,; et al. (Jabatan Kesihatan Masyarakat, Pusat Universiti Kebangsaan Malaysia, 2017)
Introduction Congenital malformations (CM) comprise a wide range of abnormalities of body structure or function that are present at birth and are of prenatal origin. It has contributed to a significant proportion of infant morbidity and mortality. The aims of this study were to determine the extent and investigate the relationship between CM and its associated demographic variables. Methods Data was extracted from Ministry of Health (MOH) database compiled from the reports on Stillbirth & Under 5 Mortality from year 2013 to 2014. Results Out of 9,827 child death, 2,840 (28.9%) were classified under CM as defined under ICD-10 classification. Majority of those with CMs died at neonatal stage (62.7%) and among mothers aged between 20 to 35 years old (67.3%). The mean age of mothers among CM children was 30.8±6.5 years old. Approximately 5.8%, 6.7% and 3.3 % of total CM were neural tube defects, heart defects and hydrops fetalis respectively. The prevalence of CM in males was 15% higher than females. The difference were evident between CM and age of death of children under 5 years old (p<0.001) as well as between CM and maternal age groups (p<0.001). Conclusions CM is responsible for 28.9% of total causes of child death with higher occurrence of malformation in males. A significantly higher risk of CMs among mother aged between 20 to 35 years old was observed. This emphasises the importance of raising awareness and the need to strengthen appropriate response for surveillance and prevention program of common CM in Malaysia.